The Struggle of Sultan Babullah in Expelling Portuguese from North Maluku - Setiawan, Johan; Kumalasari, Dyah (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2019)
This research was aimed at knowing Sultan Babullah’s struggle in expelling Portuguese from North Maluku in year 1570-1783. This research employed history method with the following steps (1) heuristic (2) source critic (3) interpretation (4) historiography. The research results were: (1) The murder of Sultan Khairun that was done by Antonio Pimental ordered by Diego Lopez de Masquita was the cause of resistance arising as well as eviction that was done by Sultan Babullah to Portuguese, (2) Babullah struggle started when he was inducted as Sultan of Ternate in 28th of February 1570. During his induction he swore to take revenge on his father’s death. Babullah flamed Soya-soya war or land liberation war. Portuguese’s posts were destroyed. Portuguese’s defense fortresses were taken down one by one except Gamlamo Fortress, (3) The final struggle of Babullah was when Gamlamo Fortress as Portuguese’s defense fortress was encircled for five years from 1570-1575, until Portuguese surrendered and was evicted from North Maluku.